PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS VB SDN 008 BUKIT KAYU KAPUR - Muhammad Syukron Syukron; Munjiatun '; Mahmud Alpusari Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This Research represent the Research of Class Action (CAR) conducted to increase result of learning student of class of VB SDN Bukit Kayu Kapur by applying model the study of Role Playing. This Research is done at April  2014 executed by 2 cycle. this Subjek Research  is student of class of VB SDN 008 Bukit Kayu Kapur amounting to 24 one who is made by a data source. Instrument of data collecting at this research is sheet of activity perception learn and student and also result of learning. Mean of result of learning previous student that is 58,7 from 24 complete student people only 9 completely is klasikal 37,5% while student which is not complete 15 people completely is klasikal 62,5%. At this research is presented by a activity percentage learn and student and also result of daily restating of cycle of I and cycle II. Activity Percentage learn at cycle of I and II  is  60% mounting to become 95%. percentage of student Activity of at cycle of I and II is 65% mounting to become 92,5% Mean of  result of learning student  of at  cycle I is  63 from 24 student, complete 12 people with the percentage 50% and which is not complete 12 people with the percentage 50%. Mean  of  result of learning student of cycle II  is  80,2 from 24 one who complete 22 people with the percentage 92%. Inferential thereby that this research hypothesis that is if applied  by  model of study of Role Playing hence can improve the result learn the student of class of VB SDN 008 Bukit Kayu Kapur accepted. Keywords : Model The Study of Role Playing, Result of Learning PKN